2015
DOI: 10.1007/s00774-015-0716-9
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density of postmenopausal women with rheumatoid arthritis depends on disease duration regardless of treatment

Abstract: The aim of this study was to determine the associations of disease activity and disease duration with the bone mineral density (BMD) in rheumatoid arthritis (RA) patients. We also evaluated the associations of biological drugs with bone loss. A total of 138 postmenopausal RA patients were retrospectively assessed to identify the associations of disease activity, disease duration, and biological drug use with BMD. We assessed the associations of disease duration, a C-reactive protein based disease activity scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 21 publications
2
23
1
2
Order By: Relevance
“…Our findings showed that a risk factor for femoral neck BMD reduction was a short disease duration. There is a discrepancy between our results and the findings of previous reports [ 18 , 31 ]. Bone loss was observed in patients with recently diagnosed rheumatoid arthritis, suggesting that the start of the femoral neck bone loss may be much earlier than previously anticipated [ 32 ].…”
Section: Main Textcontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings showed that a risk factor for femoral neck BMD reduction was a short disease duration. There is a discrepancy between our results and the findings of previous reports [ 18 , 31 ]. Bone loss was observed in patients with recently diagnosed rheumatoid arthritis, suggesting that the start of the femoral neck bone loss may be much earlier than previously anticipated [ 32 ].…”
Section: Main Textcontrasting
confidence: 99%
“…Several studies showed that glucocorticoid therapy increase intensely risk of vertebral fracture [ 28 30 ]. Mori et al reported in a multivariate linear regression analysis that longer RA disease duration was significantly related to the loss of BMD in the femoral neck and total femur [ 31 ]. Our findings showed that a risk factor for femoral neck BMD reduction was a short disease duration.…”
Section: Main Textmentioning
confidence: 99%
“…However, our patients had a longer disease duration and lower baseline T-scores. In a previous study, the disease duration was inversely associated with BMD in female patients with RA [ 30 ]. Disease activity predicts bone loss in early RA [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the inter-species differences between mice and humans in inflammatory mechanisms, the bone turnover is regulated by the immune system in a similar manner. Therefore, different chronic inflammatory comorbid conditions, including rheumatoid arthritis and diabetes, were shown to induce an osteopenic phenotype in both species [60][61][62][63][64][65]. The acute inflammation associated with concomitant trauma also influences fracture healing both in humans and in rodents [5••, 48•, 66, 67].…”
Section: Murine Disease Models Used In Fracture Healing Researchmentioning
confidence: 99%